The Effect of a Group Counseling Program Based on ‎Cognitive- Behavioral Play Therapy in Reducing ‎Emotional and Behavioral Problems among a Sample of ‎Syrian Refugee Students‎ - Alaedein, Jehad; Alhawamdeh‎, Shadi (Jordan Journal of Educational Sciences, 2021)
This study sought to examine the effect of a group counseling program based on cognitive- behavioral play therapy in reducing emotional and behavioral problems among a sample of male Syrian refugee students enrolled in Abd Al-Malik Ibn Marwan Elementary School for Boys, Al-Mafraq, Jordan. The sample consisted of (40) students in the sixth and seventh grades, with ages ranging between (12-14 years) and selected according to their higher scores on the Arabic version of the Strengths and Difficulties Questionnaire. (SDQ). The sample was randomly divided into two groups: The experimental treatment group that received the group counseling program based on CBPT and the control group whose members did not participate in any counseling intervention. The results indicated that there are statistically significant differences in the average scores between the experimental and control groups in the post-test on the Strengths and Difficulties Questionnaire (SDQ) and its five dimensions: Emotional symptoms, relationships with peers, behavioral problems, lack of attention and hyperactivity and lack of positive social behavior, in favor of the experimental group. Also, the results of the comparison between the post-test and the follow-up test for the experimental group showed that there are statistically significant differences between the scores on the study’s scale and its five dimensions, with the exception of the behavioral problems dimension, in favor of the follow-up test, where the students’ scores decreased to become significantly lower compared to their post-test scores